KETIDAKSANTUNAN KOMENTAR WARGANET PADA BERITA KAMPANYE PEMILIHAN KEPALA DAERAH INDONESIA TAHUN 2024 DI MEDIA SOSIAL - Yulianto, Eko; Rokhayati, Reni; Agustin, Yulia; Nafilah, Ila (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Based on the discussion described above, it can be concluded that the language impoliteness carried out by netizens in the comments column on social media during the 2024 regional elections is in accordance with Culpeper's theory. Language impoliteness threatens negative face in the form of actions that result in the person speaking to not agreeing to do something, giving rise to an attitude of commanding, ridiculing, giving advice, giving advice, reminding, threatening, warning and opposing. Actions that threaten the positive face of the interlocutor include actions that show a negative assessment of the interlocutor resulting in expressions of disagreement, criticism, degrading actions, complaints, anger, accusations, insults, actions that show the speaker's indifference towards the interlocutor in the form of conflict, disagreement or challenge, impolite emotions and expressions, as well as actions that use expressions regarding names. A study using Culpeper's theory found that impolite language behavior is related to direct impoliteness (40%), sarcasm (30%) and withholding politeness (30%).